INDICATORS OF MULTIPLE INTELLIGENCE THEORY IN THE KARATE KID MOVIE (2010): PSYCHOLOGY EDUCATION - Fadhil, Muhammad; Prastiwi, Yeny (Universitas Islam Sumatera Utara (UISU), 2024)
This research aimed to identify and analyze the indicators of multiple intelligence theory as depicted in the movie The Karate Kid (2010). The researchers employed a documentation method for data collection and applied Howard Gardner's theory of multiple intelligences, proposed in 1983, to validate their findings. To introduce innovative approaches for enriching educational materials, the study also reviewed previous research on multiple intelligence theory. Utilizing a descriptive qualitative methodology, the research thoroughly examined the movie’s content. The results indicated that six out of Gardner's nine intelligence indicators were illustrated in various scenes: spatial (visual) intelligence, musical (audio) intelligence, bodily-kinesthetic intelligence, interpersonal intelligence, intrapersonal intelligence, and naturalistic intelligence. These findings underscore the diverse ways in which multiple intelligences can be represented and recognized within cinematic narratives, providing a valuable framework for educational and psychological applications. The research highlights the potential of films like The Karate Kid as effective tools for demonstrating and teaching the principles of multiple intelligences, thereby enriching educational practices and supporting holistic development.